Accuracy of Demirjian’s and Cameriere’s Methods for Age Estimation in 6- to 10-Year-Old Iranian Children Using Panoramic Radiographs - S. Milani; M. Shahrabi; H. B Fakhar; S. Parvar; M. Abdolahzadeh (International Journal of Dentistry)
Objective. This study assessed the accuracy of Demirjian’s and Cameriere’s methods for age estimation in Iranian children using panoramic radiographs. Materials and Methods. This cross-sectional study evaluated 212 panoramic radiographs of 6- to 10-year-old children retrieved from the archives of an oral and maxillofacial radiology department from 2011 to 2017. The chronological age of children at the time of radiography was determined by subtracting the date of radiography from their birth date. The developmental stage of 7 permanent left mandibular teeth was determined according to Demirjian’s method. The stage of dental maturation was determined according to Cameriere’s method by using the normalized values for 7 permanent left mandibular teeth and the number of teeth with complete root development. The error value of the two methods was calculated by comparing them with the actual chronological age of male and female children, and the absolute error values of the two methods were compared with paired t-tests. Results. The mean error value of Demirjian’s and Cameriere’s methods was found to be 0.84 and −0.06 in girls and 0.93 and 0.04 in boys, respectively. Significant differences were noted in the absolute error of the two methods compared with the chronological age of male and female children (both Ps<0.001). Conclusion. In conclusion, this study indicated that Cameriere’s method was more accurate than Demirjian’s method for age estimation in Iranian children.